Swisscollections (2021)
[Dt.:] swisscollections ist ein zentraler Sucheinstieg zu historischen und modernen Sammlungen in Schweizer Bibliotheken und Archiven und erleichtert das Auffinden und Bestellen von Handschriften, Briefen, Alten Drucken, Rara, Archivbeständen und Nachlässen, Bild- und Kartenmaterialien, Musikalien und Tonträgern aus 14 Institutionen. - [Engl.:] swisscollections is a central search gateway to historical and modern collections in Swiss libraries and archives and makes it easy to find and order manuscripts, letters, old prints, rare books, archive holdings and bequests, image and map materials, music and sound recordings from 14 institutions.